Youth, money, and behavior: the impact of financial literacy programs - Mancone, Stefania; Tosti, Beatrice; Corrado, Stefano; Spica, Giuseppe; Zanon, Alessandra; Diotaiuti, Pierluigi (Frontiers in Education, 2024)
This narrative review critically examines the scope and impact of financial literacy programs targeted at children and adolescents. By synthesizing findings from diverse studies, the review identifies key components of effective financial education, including the integration of experiential learning, the role of digital tools, and the importance of parental involvement. Challenges such as ensuring curriculum relevance in a rapidly evolving financial landscape and addressing the varied learning needs of young populations are discussed. Recommendations for future research include the necessity for longitudinal studies to assess the long-term effects of early financial education and exploration into the digitalization of financial literacy. This review aims to contribute to the development of more inclusive, adaptive, and impactful financial literacy education strategies, underscoring the critical role of comprehensive financial education in preparing young individuals for financial autonomy and resilience.